Analisis keterampilan dasar mengajar guru pada mata pelajaran IPS kelas IV sekolah dasar - Safira, Theresa Shita; Istiyati, Siti; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2021)
The purpose of this research is to analyze the basic teaching skills of teachers in the fourth grade social studies subject at SDN Dukuhan Kerten No.58 Surakarta. Basic teaching skills are vital to be possessed and dominated by an teacher in the learning process. This study is a qualitative examination with a descriptive technique utilizing a phenomenological approach. The strategy of taking the subject utilized was purposive sampling method. Teacher, students, and headmaster as a source of data. Data collections using observation, interview, questionnaries, and documentation. The data validity test was using triangulation method. The data that has been obtained were analyzed using the Miles and Huberman model to analyze the completion steps in accordance with the indicators of basic teaching skills. The result analyze of the investigation show that the teacher has dominated 8 basic teaching skills, including: basic and advanced questioning skills, the teacher has paid attention to how to ask questions to students properly and correctly. In affirming skills, the educator has given verbal support. In the application of the skills to variation, the teacher has utilized learning media as pictures to help the learning process. In explaining skills, in explaining the teacher emphasizes the important points to be conveyed on to students. For the skills of opening and closing lessons, the teacher has likewise executed it well, the teacher gives inspiration to follow-up as every day assessments for every exercise. The application of small group discussion guiding skills, the teacher divides students into groups, organizing group discussions, observe and supervise each group, and concentrates of student in the group. In applying the class management skills, the teacher consistently gives oversight to student in the classroom. And on the application of small group and/or individual teaching skills, the teacher has set up great associations with student and parents of student to facilitate the learning process both at school and at home